Discharge planning for heart failure patients in a tertiary hospital in Shanghai: a best practice implementation project. (February 2016) - Chen, Yu; Zhu, Li; Xu, Fei; Chen, Jun
Executive summary : Background : Heart failure is a major public health concern which contributes significantly to rising healthcare costs. Comprehensive discharge planning can improve health outcomes and reduce readmission rates which, in turn, can lead to cost savings. Objectives : The aim of this project was to promote best practice in the discharge planning of heart failure patients admitted in the coronary care unit of Zhongshan Hospital. Methods : A clinical audit was undertaken using the Joanna Briggs Institute Practical Application of Clinical Evidence System tool. Five audit criteria that represent best practice recommendations for heart failure discharge planning were used. A baseline audit was conducted followed by the implementation of multiple strategies, and the project was finalized with a follow‐up audit to determine change in practice. Results : Improvements in practice were observed for all five criteria. The most significant improvements were in the following: completion of a discharge checklist (from 0% to 100% compliance), comprehensive (i.e. inclusion of six topics for self‐care) discharge education for patients (from 7% to 100% compliance), and conducting a telephone follow‐up (from 0% to 76% compliance). The compliance rates for the two remaining criteria, completion of a structured education for patients and scheduling an outpatient clinic visit, both increased from 93% to 100%.Strategies that were implemented to achieve change in practice included development of a local discharge planning checklist, provision of training for nurses, and development of resources. Conclusions : The project demonstrated positive changes in the discharge planning practices of nurses in the coronary care unit of Zhongshan Hospital. A formalized discharge planning is currently in place and plans for sustaining practice change are underway. A continuous cycle of audit and re‐audit will need to be carried out in the future to determine the impact of this evidence implementation activity on heart failure patient outcomes.